Flow pattern and mechanism of the transformation of upward gas-liquid two-phase flow in vertical tubes under heaving vibration - Zhou, Yunlong; Li, Yuqing; Liu, Qichao; Chang, He; Zhang, Shibo; Chen, Cong (International communications in heat and mass transfer, 2025)
Gas-liquid two-phase flow in vertical tubes is critical to the operation safety of steam generators in floating nuclear power plants, which are subject to heaving vibration induced by ocean waves. However, the flow patterns and transition mechanisms under such dynamic conditions remain insufficiently understood, limiting accurate prediction of flow and heat transfer characteristics. This study experimentally investigated the gas-liquid two-phase flow pattern and mechanism of the transformation of vertical tube under heaving vibration. Five flow patterns were identified, including bubble flow, slug flow, churn flow, annular flow, and a newly discovered stagnant flow. Flow pattern maps were constructed to reveal how tube diameter, vibration frequency, and amplitude affect transition boundaries. Existing transition models for static and rolling conditions were found to be inapplicable. New models incorporating vibration parameters were developed, yielding average errors of 13.24 % for bubble to slug flow, 9.96 % for slug to churn flow, and 15.25 % for churn to annular flow transitions. These findings advance the understanding of oscillating gas-liquid two-phase flows by identifying a novel flow pattern and establishing validated transition models specific to heaving vibration, providing essential theoretical support for flow pattern prediction and parameter design in floating nuclear power systems.